2012
DOI: 10.1016/j.bbamcr.2012.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine 1-phosphate induces MKP-1 expression via p38 MAPK- and CREB-mediated pathways in airway smooth muscle cells

Abstract: Sphingosine 1-phosphate (S1P), a bioactive sphingolipid elevated in asthmatic airways, is increasingly recognized as playing an important role in respiratory disease. S1P activates receptor-mediated signaling to modulate diverse cellular functions and promote airway inflammation. Although many of the stimulatory pathways activated by S1P have been delineated, especially mitogen-activated protein kinases (MAPK), the question of whether S1P exerts negative feedback control on its own signaling cascade via upregu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
51
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 23 publications
10
51
0
Order By: Relevance
“…We here found that CpdA-induced up-regulation of the antiinflammatory protein MKP-1 was crucial for the inhibition of cytokine-induced CXCL10 (Figure 7). Previous studies have confirmed the antiinflammatory potential of GC-inducible MKP-1 in human ASM cells (26,31,36). Our data strongly implicate MKP-1-sensitive MAPK pathways in the regulation of CXCL10 in ASM cells.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…We here found that CpdA-induced up-regulation of the antiinflammatory protein MKP-1 was crucial for the inhibition of cytokine-induced CXCL10 (Figure 7). Previous studies have confirmed the antiinflammatory potential of GC-inducible MKP-1 in human ASM cells (26,31,36). Our data strongly implicate MKP-1-sensitive MAPK pathways in the regulation of CXCL10 in ASM cells.…”
Section: Discussionsupporting
confidence: 72%
“…We did confirm that CpdA had no transactivation potential by its failure to induce the GILZ gene (Figure 3). The transient induction by CpdA of MKP-1, another GC-inducible early gene, can be easily explained by the implication of GRa-independent mechanisms because MKP-1 up-regulation in ASM could be induced by TNF-a (36), sphingosine 1-phosphate (26), and b2 agonists (37). We found that induction of MKP-1 was also seen at the protein level.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…MKP-1 is a MAPK deactivator with multiple modes of anti-inflammatory action: it is an endogenous protein that functions as a negative feedback effector to repress MAPK-mediated proinflammatory signaling and cytokine secretion (7,19), and it can be upregulated by anti-asthma medicines such as ␤ 2 -agonists and corticosteroids (8,20,21,27,28), serving as an important way in which these front-line asthma medicines achieve their anti-inflammatory function.…”
mentioning
confidence: 99%